Pengaruh Komunikasi Interpersonal Tour Guide Terhadap Kepuasan Pengunjung Di Curug Cikuluwung - Febri Palupi Muslikhah; Erna Ernawati; Syamsul Rizal (Institut Agama Islam Sahid (INAIS) Bogor, 2022)
This study aims to determine the influence of interpersonal communication tour guides on visitor satisfaction at Curug Cikuluwung Bogor, how much influence interpersonal communication tour guides on visitor satisfaction at Curug Cikuluwung Bogor. This research is a descriptive quantitative research, namely searching for data or information from the reality of the existing problems by referring to the proof of the concept or theory used which was carried out on visitors to the Cikuluwung waterfall and was selected using accidental sampling with 100 respondents. Based on the data obtained and the results of the analysis that has been done, it can be concluded about the influence of interpersonal communication tour guides on visitor satisfaction at Curug Cikuluwung, namely based on the results of the t test shows a p-value of 0.000 (0.000 <0.05) then the alternative hypothesis (Ha) accepted and the null hypothesis (H0) is rejected, it means that there is an effect of interpersonal communication on visitor satisfaction Curug Cikuluwung Bogor (Y). based on the results of the determination test the value of the Adjusted R Square coefficient generated by the independent variable is 0.370, which means it is 37%. This shows that the higher the interpersonal communication the higher the level of visitor satisfaction